Running economy and lower extremity stiffness in endurance runners: A systematic review and meta-analysis - Liu, Bowen; Wu, Jinlong; Shi, Qiuqiong; Hao, Fengwei; Xiao, Wen; Yu, Jingxuan; Yu, Fengyu; Ren, Zhanbing (Frontiers in Physiology, 2022)
Background: Lower extremity stiffness simulates the response of the lower extremity to landing in running and jumping tasks. Although lower extremity stiffness has a significant role in human running tasks, the relationship between lower extremity stiffness and energy expenditure remains controversial. This study aims to explore the relationship between running economy and lower extremity stiffness. Methods: This study utilized articles from the Web of Science, PubMed, and Scopus discussing the relationships between RE and indicators of lower limb stiffness, namely vertical stiffness, leg stiffness, and joint stiffness. Methodological quality was assessed using the Joanna Australian Centre for Evidence-Based Care (JBI). Pearson correlation coefficients were utilized to summarize effect sizes, and meta-regression analysis was used to assess the extent of this association between speed and participant level. Result: In total, 13 studies involving 272 runners met the inclusion criteria and were included in this review. The quality of the 13 studies ranged from moderate to high. The meta-analysis results showed a negative correlation between vertical stiffness (r=-0.520, 95% CI, -0.635 to -0.384, P<0.001) and leg stiffness (r=-0.568, 95% CI, -0.723 to -0.357, P<0.001) and RE. Pooled results from the two studies showed a small negative correlation between knee stiffness and RE. Meta-regression results showed that the extent to which leg stiffness was negatively correlated with RE was influenced by speed (coefficient=-0.409, P=0.020, r2=0.79) and participant maximal oxygen uptake (coefficient=-0.068, P=0.010, r2=0.92). Conclusion: The results of this study suggest that vertical, leg, and knee stiffness are important factors influencing RE. We found that high vertical and knee stiffness was related to better RE. However, experience and speed will determine whether a runner can improve leg spring stiffness to reduce energy expenditure.